RHEOLOGICAL AND MICROSTRUCTURAL EVOLUTION OF CARRARA MARBLE WITH HIGH SHEAR STRAIN: RESULTS FROM HIGH TEMPERATURE TORSION EXPERIMENTS - Pieri M.; Burlini L.; Kunze K.; Stretton I.; Olgaard D.L. (My University, 2001)
This study investigated the rheological and microstructural evolution of Carrara marble deformed to large shear strain to understand how dynamic recrystallization and lattice-preferred orientation (LPO) are related to strain softening processes. Solid cylinders of Carrara marble were deformed in torsion up to a shear strain of γ=11 at constant twist rates, which correspond to a shear strain rate of 3×10−4 s−1 at the outer surface, and at temperatures of 1000 and 1200 K (727 and 927°C, respectively). For the initial grain size of 150 μm, these conditions are within the dislocation creep regime.Substantial changes in both rheology and microstructure were observed as the marble deformed to high shear strain at 1000 K (1200 K). A peak stress was reached at about γ=1 (γ=0.5) followed by moderate strain weakening. An apparent steady-state flow stress was obtained at high shear strain of γ>5 (γ>2). The stress exponent n decreased slowly with strain from 10 (γ=1) to 6 (γ=9) at 1000 K, but it remained approximately constant at 1200 K (n around 10). At the maximum reached shear strain of γ=11 (γ=8.5), the marble had almost completely recrystallized to a fine grain size of about 10 μm (20 μm). A secondary foliation developed in the recrystallized matrix, which is at a large oblique angle to the shear zone boundary (SZB). LPO was measured by electron backscatter diffraction (EBSD). For both temperatures, the LPO evolved from an oblique deformation texture to a very sharp and symmetric single orientation component with r{101̄4} parallel to the shear plane and a〈1̄21̄0〉 parallel to the shear direction. It is concluded that strain weakening was associated with the development of a strong LPO during dynamic recrystallization to a finer grain size. Mechanical and microstructural steady-state is only reached at large shear strain. The steady-state lattice and grain shape fabrics can hardly be used as shear sense indicators in such recrystallized calcite mylonites.